Penanaman Sikap Cinta Tanah Air dalam Pramuka di Dabin 5 UPTD Pendidikan Wirosari Brobogan - Sunu Dwi Priyoutomo; Abdul Ngalim; Suyatmini Suyatmini (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study was to describe the attitude of patriotism planting in extracurricular activities scouts on the General Terms and Conditions Skills Special Skills in Dabin 5 UPTD Wirosari Subdistrict Grobogan. Type ethnographic qualitative research design. The research subjects principals, teachers and students. Data collection techniques with interviews, observation, and documentation. Data analysis techniques to the analysis of the flow of the process of data collection, data reduction, display, and verification, conclusion. The validity of the data sources and data triangulation. The research result is habituation attitude of patriotism at the General Proficiency Requirements can memorize at least three daily prayers, prayers can carry, can maintain the cleanliness of the room school or place of worship, is able to help someone in the vicinity, following the flag ceremony with wisdom. Exemplary attitude of patriotism at the General Proficiency Requirements can use Indonesian well and correctly, not littering, can show true deference to the Red and White Flag, can be memorized to sing the national anthem Indonesia Raya. SKK is used to apply the attitude of patriotism is SKK singer, conductor SKK, SKK P3K, SKK Explorer / Searching for Traces, SKK Camping, SKK Greening.